Mathematical teaching resources for hospital classrooms in Ecuador - Pinos-Benavides, Ximena (2025)
Children and young people facing chronic or long-term illnesses often find their academic education interrupted. To address this need, hospital classrooms have emerged as an alternative that guarantees continuity of learning. Mathematics is one of the most complex disciplines and faces several challenges, requiring adaptation to innovative teaching resources that maintain student motivation and interest. Ecuador's official curriculum establishes learning standards that must be met even in hospital settings. This highlights the need for curricular adaptations to respond to students' unique conditions. The purpose of this study is to investigate which teaching resources support mathematics learning. This is an exploratory qualitative study, supported by the empirical method, that is, the researcher's direct experience. The results obtained from the interview script indicate that among the teaching techniques applied in the hospital setting, the visual and motor channels prevail, through the use of graphic materials, pictorial representations, and body dynamics. These techniques allow the abstract contents of Mathematics to become meaningful sensory experiences, enhancing learning and adapting to cognitive needs and styles.